INVESTIGATING LEADERSHIP APPROACHES TO BOOST INTERNATIONAL STUDENT ENROLLMENT FOLLOWING FINANCIAL MERGERS IN ACADEMIA - Lee, S.H.; J., Kim (Ayden International Journal of Banking, Finance and Technology, 2024)
This study examines the impact of merger and acquisition (M&A) activities on nonresident alien rates in higher education institutions (HEIs) in the United States. The study utilized an Event Study theoretical framework to conduct a quantitative causal-comparative analysis to determine if there was any significant interaction effect between time and merger status upon revenues, fall enrollment rates, and nonresident alien rates for Title IV HEIs. The study found that nonresident alien rates did not significantly increase due to M&A activities and that other factors caused growth in nonresident alien rates apart from M&A activity. It recommends that the most effective means to improve nonresident alien rates lie elsewhere. The article suggests that M&A initiatives may not cause an immediate boost in brand recognition in the international arena. This research contributes to the literature by offering a rigorous analysis of the merger effects on HEIs and recommending benchmarks for future research.